Case report and literature review: fatal cerebral fat embolism following facial autologous fat graft - Cheng, Yawen; Yan, Gezhi; Li, Chenyang; Han, Xiangning; Shang, Jing; Shang, Suhang; Han, Jianfeng; Luo, Guogang; Liu, Fude (Frontiers in Neurology, 2023)
Background Severe cerebral artery embolism is a rare complication of facial autologous fat injection. However, its incidence has markedly increased with the recent rise in facial cosmetic procedures. Case presentation We report a 31-year-old Chinese woman who presented with unconsciousness 6 h after having undergone a facial autologous fat injection. A neurological examination revealed stupor, bilaterally diminished pupillary light reflexes, right-sided central facial palsy, and no reaction to pain stimulation of right limbs. Diffusion-weighted imaging displayed patchy hyperintense lesions in the left frontal, parietal, and temporal lobes. Magnetic resonance angiography demonstrated fat embolism in the left internal carotid artery, anterior cerebral artery, and middle cerebral artery. We immediately performed mechanical thrombectomy under sufficient preoperative preparations but failed to achieve complete recanalization. Pathological examination of the embolus confirmed the presence of adipocytes. Although we actively administered symptomatic and supportive treatments, the patient eventually died due to the progression of cerebral herniation and systemic infection. Conclusion Due to the ineffectiveness of current treatment and the inferior prognosis, fat embolism, a severe complication of autologous fat graft, should draw the attention of both plastic surgeons and neurologists so that actions may be taken for both its prevention and treatment.